Between material and immaterial patrimony: The Japanese Cemetery in Alvares Machado, Sao Paulo - Nascimento, Rodrigo Modesto [UNESP] (Assoc Servidores Arquivo Nacional, 2016)
This article proposes a discussion about the relationship between the intangible heritage and material in overturning study Japanese Cemetery, located in Alvares Machado, within the municipality of Sao Paulo. The article is divided into three main parts: the first present the theoretical discussions on intangible heritage, then analyze the state registration of the cemetery and, finally, the relationship between the material and the immaterial.
Keywords: Cultural heritage; Japanese immigration; ethnic memory